Cellular Automata Based Real-Time Path-Planning for Mobile Robots. (1st July 2014) - Syed, Usman Ahmed; Kunwar, Faraz
Intelligent mobile robotic agents demand optimal motion planners with minimal query time. Most contemporary algorithms lack one of these two required aspects. This paper proposes an efficient path-planning scheme based on cellular automata (CA) that generates optimal paths in the minimum time. A Cellular automaton is evolved over the entire search space and subsequently used for the determination of the shortest path. This approach generates a parent-child relationship for each cell in order to minimize the search time. Performance comparisons with A*, Dijkstra's, D* and MPCNN have proven it to be time-efficient. Analysis, simulation and experimental results have proven it to be a robust and complete path-planning scheme. Also it has demonstrated to be time-efficient in both static and dynamic environments.